Multimodal strategy for the management of sphenoid osteoradionecrosis: Preliminary results. Issue 1 (22nd January 2020) - Daoudi, Hannah; Labeyrie, Marc A.; Guillerm, Sophie; Delanian, Sylvie; Guichard, Jean‐Pierre; Jourdaine, Clément; Faivre, Sandrine; Gauthier, Helene; Ferrand, François‐Régis; Verillaud, Benjamin; Herman, Philippe
Abstract: Objective: Osteoradionecrosis (ORN) of the sphenoid is a rare but potentially lethal complication that can occur after irradiation of nasopharyngeal and clival malignancies. The objective of this study was to describe a multimodal treatment strategy tailored to the clinical signs and to the radiological extent of the disease, and to report on its preliminary results. Methods: Retrospective monocentric study at a tertiary skull base center. Patients treated for a sphenoid ORN from January 2014 to August 2018 were identified and charts were retrospectively reviewed for demographics, histologic tumor type, previous treatments of the tumor, clinical signs at presentation, radiological data, treatment, and outcomes. Sphenoid ORN was treated by a combination of medical therapy, endovascular treatment, and/or surgery. The use of each of these therapeutic modalities was based on the extent of ORN and on the presenting signs. Results: Seven patients were included: four patients underwent endovascular treatment with occlusion of the internal carotid artery, five patients underwent surgical debridement, and covering of the exposed bone by a local flap, seven patients received antibiotics (in combination with pentoxyphilline, tocopherol, and clodronate in one case). Three patients died after progression of the ORN. The global survival rate was 57% (4/7) with a mean follow‐up of 24 months. In one case, ORN was treated successfully by medical treatment only, with a combination of antibiotics, pentoxyphilline, tocopherol, and clodronate. Conclusion: This retrospective study describes the results of a management strategy adapted to the extent of the disease in sphenoid ORN and based on medical therapy only, or on a combination of medical therapy, interventional radiology, and/or surgery. Level of evidence: 4 Abstract : This study reports on 7 cases with sphenoid ORN and their management by a combination of medical therapy, endovascular treatment and/or surgery. The global survival rate was 57% (4/7) with a mean follow‐up of 24 months. One patient was successfully treated by medical treatment only, with a combination of antibiotics, pentoxyphilline, tocopherol and clodronate.